2013
DOI: 10.1186/1471-2369-14-136
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis with erythropoietin versus placebo reduces acute kidney injury and neutrophil gelatinase-associated lipocalin in patients undergoing cardiac surgery: a randomized, double-blind controlled trial

Abstract: BackgroundCardiac surgery-associated acute kidney injury (CSA-AKI) is a common complication following coronary bypass graft (CABG) surgery. Multi-factorial causes of CSA-AKI involve oxidative stress and inflammation. Erythropoietin (EPO) has been shown from many studies to have a reno-protective effect. The present study was conducted to examine the role of EPO in preventing CSA-AKI.MethodsThis prospective, randomized, double-blind, placebo-controlled trial was conducted in the Cardiovascular and Thoracic Unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 50 publications
0
67
0
Order By: Relevance
“…Patients, all medical staff, & investigators were blinded to treatmentLow risk: Data Safety Monitoring Board with unmasking followed recording of the final AEs of the patient last enrolledLow riskLow risk: lost patients reportedLow risk: but 1 patient withdrewKim 2013 [27]AKI: DB, SSLow risk: computer-generated random codeLow risk: medications were prepared by a nurse who knew the patient’s group assignment but was not involved in the studyUnclear riskLow risk: No dropoutsLow risk: lost patients reportedLow risk: all patients treatedOh 2012 [16]AKI: DB, SSLow risk: A randomization code list with a block size of two was generated. Treatments were allocated to patients through the Internet in accordance with the predefined randomization listLow risk: a research coordinator performed randomization and prepared the study drugsUnclear riskLow riskLow risk: all patients completed the trialLow risk: all patients completed the trialTasanarong 2013 [28]AKI: DB, SSLow risk: treatment assignment by blocked randomization. Sealed envelopes containing the allocation group were opened by nurses who did not participate in the studyLow risk: treatments were blindly given to the research coordinator.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients, all medical staff, & investigators were blinded to treatmentLow risk: Data Safety Monitoring Board with unmasking followed recording of the final AEs of the patient last enrolledLow riskLow risk: lost patients reportedLow risk: but 1 patient withdrewKim 2013 [27]AKI: DB, SSLow risk: computer-generated random codeLow risk: medications were prepared by a nurse who knew the patient’s group assignment but was not involved in the studyUnclear riskLow risk: No dropoutsLow risk: lost patients reportedLow risk: all patients treatedOh 2012 [16]AKI: DB, SSLow risk: A randomization code list with a block size of two was generated. Treatments were allocated to patients through the Internet in accordance with the predefined randomization listLow risk: a research coordinator performed randomization and prepared the study drugsUnclear riskLow riskLow risk: all patients completed the trialLow risk: all patients completed the trialTasanarong 2013 [28]AKI: DB, SSLow risk: treatment assignment by blocked randomization. Sealed envelopes containing the allocation group were opened by nurses who did not participate in the studyLow risk: treatments were blindly given to the research coordinator.…”
Section: Resultsmentioning
confidence: 99%
“…sCr at 2 weeks favored the ESA arm but did not reach statistical significance ( p  = 0.054). No difference in renal recovery or renal survivalTasanarong 2013 [28]Thailand (Thammasat Chalerm Prakiat Hospital)Patients scheduled for elective CABG using CPBepoetin β (200 U/kg; Recormon) 3 d before CABG and 100 U/kg at the operation time.Same volume & schedule of 0.9% saline N  = 100: ESA(50), control(50)≥0.3 mg/dl or ≥50% increase in sCr from baseline within the first 48 h post-operation according to the KDIGO 2012 criteria.No difference in Hb. sCr increase and eGFR decrease was lower in the ESA group.…”
Section: Resultsmentioning
confidence: 99%
“…Weltert et al reported that the perioperative administration of human erythropoietin for 4 days significantly reduced blood transfusion and raised hemoglobin levels in patients undergoing off-pump CABG surgery [31]. Moreover, Tasanarong et al reported that prophylactic recombinant human erythropoietin administration before on-pump CABG surgery significantly reduced the occurrence of acute kidney injury and the length of hospital stay [32]. Although these studies did not focus on patients with CKD, their results suggest that ESA administration is a promising strategy for CAD patients with anemia and CKD.…”
Section: Discussionmentioning
confidence: 96%
“…Three observational studies in cardiac surgery found that erythropoietin (EPO)-treated patients prevented AKI [59][60][61]. However, these results could not be confirmed in an early intervention study in ICU patients and in cardiac surgery patients [62 && ,63].…”
Section: Guideline 36: Growth Factor Interventionmentioning
confidence: 99%